Hepatoprotective Potential of Schleichera oleosa Leaf Extract Against Paracetamol-Induced Liver Injury in Rats - Zulham, Zulham; Rasyid, Andi Ulfah Magefirah; Burhan, Asril (Jurnal Jamu Indonesia, 2025)
Schleichera oleosa L. is traditionally used in herbal medicine and has shown pharmacological activities such as antioxidant, anticancer, and antimicrobial effects. Its antioxidant capacity is attributed to polyphenols, which neutralize free radicals and contribute to liver protection. This study evaluated the hepatoprotective effect of S. oleosa leaf extract against paracetamol-induced liver injury in rats. Antioxidant activity was measured using the DPPH method, yielding an IC₅₀ of 11.43 µg/mL, indicating strong activity. Rats were administered 50, 100, or 150 mg/kg body weight of extract, followed by 1000 mg/kg paracetamol to induce liver damage. SGOT and SGPT levels were significantly reduced in all extract groups compared to the negative control, with the 100 mg/kg dose being the most effective. However, curcumin showed superior protection. These results suggest that S. oleosa has hepatoprotective potential, but further studies are needed to confirm its long-term safety and efficacy.